The Impact of Logistics Service Quality on Customer Satisfaction: A Case of Jingdong Mall in Xiamen City, China - Juan, Fan; Pathak , Shubham (Science, Technology, and Social Sciences Procedia, 2024)
This paper aims to explore the impact of logistics service quality on customer satisfaction at Jingdong Mall in Xiamen, China. This paper adopted quantitative research method and used “Questionnaire Star” to conduct a questionnaire survey on users of Jingdong Mall in Siming District, Xiamen City, and collected a total of 400 valid questionnaires. And use SPSS software to analyze and test the research data through descriptive statistics, correlation analysis and regression analysis. Research results show that logistics service quality has a significant and direct positive impact on customer satisfaction. This paper found that the logistics service quality of enterprises can be improved and improved through 5 aspects, including: reliability, assurance, tangibles, empathy and responsiveness. This research provides more support for enterprises to improve logistics service quality, improve customer satisfaction, enhance enterprise core competitiveness and other related developments.